Growth of amorphous, anatase and rutile phase TiO2 thin films on Pt/TiO2/SiO2/Si (SSTOP) substrate for resistive random access memory (ReRAM) device application - Alsaiari, Mabkhoot A.; Alhemiary, Nabil A.; Umar, Ahmad; Hayden, Brian E. (Ceramics international, 2020)
Memory structures play a basic role in providing integrated circuits of powerful processing capabilities. Even most powerful processors have nothing to offer without an accompanying memory and importantly, the development of mobile devices is dependent on the continual improvement of memory technology. Herein, we report the synthesis of TiO2 thin films on SSTOP (Pt/TiO2/SiO2/Si) substrate via physical vapour deposition process for the first time. The layers consisted of Si, SiO2, TiO2 and Pt, hence the SSTOP shorthand is used throughout the text. Three different phases of TiO2 thin films were obtained, i.e. amorphous, anatase and rutile phases, by controlling the reaction parameters which were examined by x-ray diffraction (XRD), scanning electron microscopy (SEM), energy dispersive spectroscopy (EDS), atomic force microscopy (AFM) and Raman-scattering spectroscopy in order to understand the crystallographic, morphological, compositional and scattering properties. The detailed studies confirmed the formation of various crystal phases of titania. The grown thin films on SSTOP substrates were further utilized to fabricate resistive random access memory (ReRAM) devices and the initial electrical screening was performed on capacitor-like structures which were prepared using platinum top electrodes (diameter = 250 μm) on a 14 × 14 array metal contact mask. Current-Voltage (I–V) measurements were implemented employing a range of current compliances (IC). The detailed electrical characterizations revealed that the forming field for a switchable unipolar device was found to be greatest on rutile titania and lowest on the amorphous titania phase. Similarity, the resistive contrast was greatest on the rutile titania phase and lowest on the anatase titania phase. Design for ReRAM device based on Pt/TiO2/SiO2/Si (SSTOP) substrate. [Display omitted]